Factors influencing track and swimming coaches` intentions to use sport psychology services - Zakrajsek, R. A.; Zizzi, S. J. (Athletic Insight - The Online Journal of Sport Psychology, 2007)
This study is the first attempt at developing an instrument measuring coaches' attitudes toward sport psychology modified from Martin, Kellmann, Lavallee, and Pages (2002) Sport Psychology Attitudes-Revised (SPA-R) form. The Sport Psychology Attitude-Revised Coaches (SPA-RC) form was developed and examined through exploratory factor analysis (EFA) procedures. In addition, an exploratory model of service use was fashioned through regression analyses to help understand coaches' intended use of sport psychology services. Coaches (n = 374) were surveyed regarding attitude, previous exposure, expectations of the consultation process, and intentions to use sport psychology services. EFA with the SPA-RC revealed a 3-factor solution (stigma tolerance, confidence in sport psychology consultation, and personal openness) accounting for 45% of the total variance. Results also showed initial support for the exploratory model, accounting for 38% of the total variance, with confidence (34%) as the most significant predictor of coaches' intentions, followed by stigma tolerance (3%), and expectations of the process (1%).